1972
DOI: 10.1677/joe.0.0540417
|View full text |Cite
|
Sign up to set email alerts
|

The Sodium and Potassium Concentrations in the Uterine Fluid of the Rat at the Time of Implantation

Abstract: Rat uterine fluid Na+ and K+ concentrations were calculated from the ratio of the Na+ and K+ concentrations in uterine washings, on the assumption that the sum of Na+ and K+ (mequiv./l) is the same in blood serum and in uterine fluid. Uterine fluid volumes were likewise calculated from the total quantity of Na+ and K+ washed out of the uterine horn.The mean uterine fluid volume was 7\m=.\6 \ g=m\ lper horn and the mean potassium concentration was 45\m=.\8 mequiv./l on day 6 of normal pregnancy. Both oophorecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…The disappearance of luminal fluid in the preimplantation period, a characteristic feature of many species (20), is considered to be a mechanism leading to the ''closure'' of the lumen, thereby enabling embryos to be held in contact with uterine epithelium before initiation of implantation. The present study has demonstrated that abnormal uterine fluid accumulation during the preimplantation period results in implantation failure, which may be a contributing factor to infertility caused by C. trachomatis infection.…”
Section: Discussionmentioning
confidence: 99%
“…The disappearance of luminal fluid in the preimplantation period, a characteristic feature of many species (20), is considered to be a mechanism leading to the ''closure'' of the lumen, thereby enabling embryos to be held in contact with uterine epithelium before initiation of implantation. The present study has demonstrated that abnormal uterine fluid accumulation during the preimplantation period results in implantation failure, which may be a contributing factor to infertility caused by C. trachomatis infection.…”
Section: Discussionmentioning
confidence: 99%
“…All values are from [31], except for uterus ion concentrations, which are from [32], and oviduct pH, which is from [33].…”
Section: Figure 2 the Ionic Environment Through Which Sperm Cells Travelmentioning
confidence: 99%
“…and implantation of the developing embryo (Clemetson et al 1972;Boldt, Casas, Whaley, Creazzo & Lewis, 1991;Fraser, 1992Fraser, , 1995. Other important functions of endometrial epithelial cells include regulation of luminal pH and uterine fluid volume.…”
mentioning
confidence: 99%